Differences in shell morphology and internal growth pattern of the Patagonian scallop Zygochlamys patagonica in the four main beds across their SW Atlantic distribution range - Lomovasky, Betina Judith (2008)
Shell morphometry, internal shell growth patterns and growth rates of the Patagonian scallop Zygochlamys patagonica from four different beds across their SW Atlantic distribution range were compared. The northern beds (Uruguay, 36°17′S and Reclutas, 39°25′) showed lower shell height, length and shell mass than the southern populations (Tango B bed: 42°30′ and Beagle bed: 55°10′S). Mean height, length, and width increased following a N-S latitudinal gradient. Acetate peels revealed the presence of internal growth bands with alternating broad opaque and narrow translucent growth bands. In the Reclutas bed, the "cluster of translucent bands" representing external rings was formed mainly during winter at the same time of the higher gonadal condition index, and a regional decrease in food availability. The growth pattern observed for the first two or three growth bands was less pronounced than other growths bands, with sizes of these individuals corresponding to first maturity of the species. Thus, differences can be due to differential allocation of energy investment to shell production between juvenile and adult organisms. The internal growth patterns and maximum age differed between beds, with an increase in the maximum age from the N to the S (Uruguay bed: 13 years old, Reclutas bed: 14 years old, Tango B bed: 20 years old, Beagle bed: 21 years old). Our study provides evidence of variation of growth in Z. patagonica in the four main beds across their SW Atlantic distribution range, where a significant increase in H∞ from N to S coincides with different internal growth pattern, maximum age and a trend toward higher von Bertalanffy k parameter in the northern beds.